Experimental Study on Improving the Compressive Strength of UHPC Turntable - Jiawei Wang; Quansheng Sun (Advances in Materials Science and Engineering)
Purpose. In the recent years, horizontal rotation methods have been widely used for bridge construction, particularly for constructing overpass bridges on highways, railways, and shipping. However, bridges constructed using the swivel construction method bear several types of loads during the rotation process. Furthermore, the bridge turntable, which is the core force-bearing component of the structure, bears considerably large vertical pressure and horizontal frictional resistance. The present research proposes three strengthening methods when applying ultrahigh performance concrete (UHPC) materials to the turntable of a spherical hinge to improve structural reliability. Furthermore, the mechanical properties of the structure are evaluated using a unidirectional compressive strength test to provide a theoretical and experimental basis for the application of the UHPC material. Design/Methodology/Approach. To evaluate the mechanical performance of the turntable of a spherical hinge, scale models of six sets of UHPC turntables—steel tube-UHPC, stirrup-UHPC, and directional steel fiber UHPC—were constructed in the study. The compressive strengths of the turntable specimens were calculated after theoretical analysis. After obtaining the load-displacement curves of the cube specimens, the force characteristics of the turntable and the failure mechanism of the structure were analyzed by observing the failure mode of the specimens. Findings. The compressive strength of the steel tube-UHPC turntable was 207 MPa, which can completely replace the traditional steel turntable. In addition, the stirrup-UHPC turntable demonstrated a significant loading effect. However, the effect of the restraint radius of the stirrup needs to be considered during the design; otherwise, the loading effect is poor. Furthermore, a directional steel fiber UHPC turntable can improve the compressive strength to a certain extent. We summarize the failure mechanism of the spherical hinge turntable specimens that are expected to play a role in UHPC spherical hinge in engineering applications and construction monitoring. Originality/Value. To the best of our knowledge, this study is the first to employ the UHPC, steel tube-UHPC, stirrup-UHPC, and directional steel fiber spherical hinge turntables in the swivel construction of bridges. The compressive strength and mechanical characteristics of the UHPC structure meet the requirements of the turntable, and more importantly, the manufacturing process (on-site pouring) of the aforementioned UHPC turntable structures is relatively simple. Finally, the manufacturing cost of the turntables is expected to be reduced by more than 50% compared to those of traditional turntables.